Serratula coronata (Asteraceae) – a new species record for the flora of Azerbaijan - Huseynova, A.Y.; Aghayeva, P.N.; Qarakhani, P.Kh.; Ali-Zade, V.M. (Український ботанічний журнал, 2019)
Serratula coronata (Asteraceae) is reported for the first time for the flora of Azerbaijan. The species was first found during the field surveys in 2012 in the forest edge near the village of Qonaqkend in Quba District of Azerbaijan, and later (in 2014) also discovered between Arafsa and Leketaq villages in the Nakhchivan Autonomous Republic. Data on distribution of species of Serratula sensu lato in the Caucasus are briefly reported and summarized. Diagnostic characters distinguishing S. coronata from other related taxa are provided. Plant communities with participation of S. coronata in Azerbaijan are characterized. Recent data on taxonomy of Serratula and related taxa are briefly discussed. Serratula coronata (Asteraceae) вперше наводиться для флори Азербайджана. Цей вид був знайдений під час польових обстежень у 2012 р. на лісовій галявині біля с. Гонагкенд у Губинському районі Азербайджана, а пізніше (в 2014 р.) – також між с. Арафса і Лекетаг у Нахічеванській Автономній Республіці. В статті стисло викладено дані про поширення видів Serratula на Кавказі. Подано діагностичні ознаки, які відрізняють S. coronata від інших споріднених таксонів. Наведено характеристики угруповань рослин із участю S. coronata в Азербайджані. Отримані результати обговорюються у контексті сучасних даних про таксономію та філогенію Serratula і споріднених таксонів.